2015
DOI: 10.15376/biores.10.3.4903-4912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Chitosan as Biopolymer Coupling Agent on the Pyrolysis Kinetics of Wood Flour/ Polyvinyl Chloride Composites

Abstract: The thermal degradation behavior and pyrolysis kinetic models of wood flour (WF)/PVC composites before and after adding chitosan were studied using thermogravimetry (TGA) and nine common kinetic model functions (f(α)). The results indicated that the thermal degradation temperature of WF/PVC composites was delayed to a higher value after adding chitosan. The first-order reaction order (L1) model and secondorder reaction order (L2) model were found to be the best reaction order functions for the description of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Moreover, CS has abundant hydroxyl and amino groups on its surface as an excellent biological coupling agent. Xu et al [2] used chitosan (CS) as a novel biopolymer coupling agent for wood flour PVC (WF/PVC) to improve interfacial adhesion properties. It was found that CS could enhance the thermal stability between WF and PVC matrix through hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CS has abundant hydroxyl and amino groups on its surface as an excellent biological coupling agent. Xu et al [2] used chitosan (CS) as a novel biopolymer coupling agent for wood flour PVC (WF/PVC) to improve interfacial adhesion properties. It was found that CS could enhance the thermal stability between WF and PVC matrix through hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%